The Flavor of Taboo: A Sociolinguistic Analysis of Sex-Food Metaphors in Indonesian and American Discourse - Sastika Seli; Ayu Oktaviani; Agus Triyogo (Institute of Advanced Knowledge and Science, 2026)
This research aims to examine how sensory perception, especially visual and olfactory features, contribute to the formation of metaphors, and to explain the sociolinguistic functions of these metaphors in humor, intimacy building, and taboos. This research is a qualitative descriptive research using the Conceptual Metaphor theory by Lakoff and Johnson. Data are sourced from the analysis of the American movie series Sausage Party: Foodtopia to analyze discourse in American English and also casual conversations of informants in the city of Lubuklinggau when using the Lubuklinggau regional language. The results show that the characteristics of food and human sexuality are shaped by cultural norms and social interactions. Speakers of the Lubuklinggau dialect use euphemisms and indirect expressions to discuss taboo topics politely, while in the American animated series, the expression of sexual symbols is explicit and exaggerate. These metaphors not only function as humor but also as a tool to build intimacy, assess gender identity, and demonstrate social power.